Structure-Activity Relationship Study of Dibenzocyclooctadiene Lignans Isolated from Schisandra chinensis on Lipopolysaccharide-Induced Microglia Activation - Hu, Di; Han, Na; Yao, Xuechun; Liu, Zhihui; Wang, Yu; Yang, Jingyu; Yin, Jun (Planta Medica, 2014)
To explore the relationship of the dibenzocyclooctadiene lignans from Schisandra chinensis to their anti-inflammatory activities, series of dibenzocyclooctadiene lignans were isolated and assessed by testing their inhibitory effects on nitric oxide production in lipopolysaccharide-induced BV2 mouse microglia. It was found, for the first time, that dibenzocyclooctadiene lignans which have S-biphenyl and methylenedioxy groups strongly inhibited LPS-induced microglia activation. The methoxy group on the cyclooctadiene introduced more effectiveness, but the presence of an acetyl group on the cyclooctadiene or hydroxyl group on C-7 decreased the inhibitory activity.
Keywords: Schisandra chinensis; Schisandraceae; dibenzocyclooctadiene lignans; microglia; nitric oxide; structure-activity relationship